miR-429 inhibits migration and invasion of breast cancer cells in vitro - YE, ZHI-BIN (Int J Oncol, 2014)
Accumulating evidence indicates that microRNAs (miRNAs) are involved in regulating cancer invasion and metastasis, and an increasing number of research demonstrates that miRNAs can promote or inhibit cell motility depending on genetic background of different cancers and the microenvironment. In the present study, we established an in vivo bone metastasis model of breast cancer by injecting MDA-MB-231 cells into the left ventricle of nude mice, and then screened the differentially expressed miRNAs between parental and bone-metastatic MDA-MB-231 cells using miRNA array. The results revealed that decreased expression of miR-429 was probably involved in negatively regulating bone metastasis of breast cancer cells. On the other hand, overexpression of miR-429 in MDA-MB-231 cells remarkably suppressed invasion in vitro. We identified ZEB1 and CRKL as potential targets of miR-429 by analyzing combined results from in silico search and global expression array of the same RNA samples. Immunoblot assay confirmed that miR-429 reduced their expression at protein level. Taken together, our results offer an opportunity for further understanding of the recondite mechanisms underlying the bone metastasis of breast cancer.